(untitled) (Research, Society and Development, 2021)
This work aims to understand the perceptions, feelings, skills and challenges of preceptors linked to the Pedagogical Residency Program (IFPI) in conducting teaching activities and providing guidance to the demands imposed by remote learning. The research is basic, observational with a quali-quantitative approach. The entire research occurred remotely and used digital communication tools when dealing with the participants. The effective participation by occurrence through the agreement to the Informed Consent Term, which guaranteed, among other things, anonymity, removal of research data at any time before publication, as well as the scientific dissemination of the results. For the collection, we used a semi-structured questionnaire produced through the Google Forms platform, subdivided into four, the first being responsible for the characterization of the profile, the second related to the perception of preceptors regarding the realization of the Pedagogical Residency program, a relation to the use of digital technologies, and finally one related to the feelings associated with remote learning. We found that despite the difficulties and the difficult time we live, as experiences related to remote teaching providing the development and improvement of teaching skills by preceptors. Additionally, the participants also report that the learning built in the first two modules of the Pedagogical Residency will serve as a basis for new strategies to be used in classroom classes. Finally, we emphasize the importance of other studies that demonstrate the impacts of remote education on basic education and the methodological changes it encourages to be experienced in face-to-face education.